Mucus glycoprotein biosynthesis in the human gall bladder: inhibition by aspirin. Issue 8 (August 1992) - Rhodes, M; Allen, A; Lennard, T W
Abstract : Aspirin, which inhibits mucin secretion in the gastrointestinal tract prevents gall stone formation in animals and may reduce gall stone recurrence in man. This study examines the effect of aspirin on mucin synthesis in human gall bladder explants. Two hundred explants were cultured with 3H-glucosamine (74 kBq/ml) for 24 hours at 37 degrees C. Mucin and other glycoproteins were isolated by papain digestion (72 hours) and exhaustive dialysis (144 hours) to remove non-incorporated radioactivity and digested protein. 3H-glucosamine was readily incorporated into glycoprotein. Pooled gall bladder explants were fractionated on a CsCl density gradient and by gel filtration on Sepharose 2B and 4B to confirm that >90% radioactivity was incorporated into mucin. Acetylsalicylic acid (230-666 micrograms/ml) significantly reduced total 3H-glucosamine incorporation (43-89%), p<0.01 (unpaired t test). Diclofenac (125-1250 micrograms/ml), similarly reduced incorporation by 45-97% p<0.001 (unpaired t test). Inhibition of mucin glycoprotein biosynthesis was irreversible with both drugs. Analysis of pooled samples on Sepharose 4B showed abolition of radioactive incorporation into mucin but no effect on incorporation into low molecular weight glycoprotein material (10% of total incorporation). This study provides a method for measuring human gall bladder mucin synthesis and shows its irreversible inhibition by acetylsalicylic acid and diclofenac at concentrations compatible with a therapeutic dose.